The Muslim World and the West: the potential of educational institutions in building bridges in the context of Malaysia - Hashim, Che Noraini; Langgulung, Hasan (2011)
The Muslim World and the West share the same global village but each has a different civilizations and worldview. Education is seen as a major vehicle in transmitting ideas, attitudes and beliefs. This paper begins with a brief history of the educational links between the West and the Muslim World and later discusses the role of educational institutions in creating barriers or building bridges between The Muslim World and the West, with special reference to Malaysia. It then discusses the fact that despite its independence from Britain in 1957, Malaysian educational institutions and systems are still influenced by the colonial educational system. In lieu of the above situation, pertinent questions have been raised, such as our consistencies in creating barriers and building bridges with the West. Finally this paper puts forward some suggestions in terms of the remedial measures to minimize the barriers and bridge the gap between West and the Muslim World.